Significance of Preoperative Systemic Immune Score for Stage I Gastric Cancer Patients - Jun Lu; Long-long Cao; Ping Li; Jian-wei Xie; Jia-bin Wang; Jian-xian Lin; Qi-yue Chen; Mi Lin; Ru-hong Tu; Chang-ming Huang; Chao-hui Zheng (Gastroenterology Research and Practice)
Background. Determining preferences regarding the benefits of adjuvant chemotherapy (AC) for stage I GC is critical. Methods. We retrospectively reviewed 1069 patients with pathologically confirmed stage I GC who underwent R0 gastrectomy between 2006 and 2014. Univariate and multivariate survival analyses were conducted. Systemic inflammation factors were used to develop a scoring system for predicting AC benefits. Results. With a median follow-up of 47 months (range 3–113 months), the 5-year overall survival (OS) rate was 90.5%. The patient score was 1 for either a pretreatment hypoalbuminemia or elevated derived neutrophil-lymphocyte ratio (dNLR) and was 0 otherwise. The SIS served as an independent prognostic factor for reduced OS. AC was delivered to 13.5% (144/1069) of all patients. Compared to surgery alone, AC had no significant effect on survival in both the entire cohort and the IA/IB subgroup. However, in the high-risk group (SIS = 2), patients with AC had a significantly better OS than those undergoing surgery alone. Conclusions. Patients with SIS = 2 may benefit from AC and thus may be considered candidates for adjuvant treatment. However, to confirm our findings, future prospective studies are warranted.